UTILIZATION OF ANTHOCYANIN IN EDIBLE FILM AS COCONUT MILK FRESHNESS INDICATOR: English - Utary Nur Rachmani Fauzan; Astrinida Rizkina Dwi Pancani; Fitria Yulistiani; Nancy Siti Djenar (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
Technology in smart packaging continues to evolve, one of which is packages equipped with food freshness indicators to monitor food safety and quality. These indicators can be formed by immobilizing anthocyanin into edible film and then changing its color to pH changes. The research aims to determine the immobilization time, test the color stability of the edible film indicator to temperature changes, determine the characterizations of the edible film indicator based on the %relative standard deviation (%RSD) value, and apply the edible film indicators as coconut milk freshness indicators. The best immobilization time was in the 90th minute with %RSD=0%. The edible film indicators did not change color from 10 to 50°C with %RSD=0%. The characterizations of edible film indicators on pH 6, 7, 8, and 10 had response times of 6.68 minutes; 9.49 minutes; 3.57 minutes; and 4.37 minutes; periods of 14 days, 13 days, 14 days, and 16 days; and good reproducibility at pH 6 and 10 and not good at pH 7 and 8. Overall, based on anthocyanin color changes, an edible film indicator can be used as a freshness indicator in coconut milk but cannot indicate the pH value of coconut milk.